Mosaicos, hiperlinks e outras dispersões: considerações sobre "Eles eram muitos cavalos" de Luiz Ruffato e "Ó" de Nuno Ramos - Gleidston Alis (2019)
This work proposes a reading of Eles eram muitos cavalos, by Luiz Ruffato, and Ó, by Nuno Ramos, through the bias of dispersion, thinking about the relations between forms and themes in the context of society called postmodern. To this aim, two conceptual operators were chosen to think about the very particular compositional processes of the two contemporary writers: the mosaic technique for Ruffato's book and the hyperlink logic for Nuno Ramos' diction. From this, we discuss the difficult framing of the two works within the scope of the textual genres and take the opportunity that these writings - open, dispersive, transgressive - offer us to choose different methodological approaches in order to analyze different thematic clipping. For this, we design relatively independent and diverse critical essays, which communicate through dialogue with the constitutive dispersion of contemporary culture and, in different ways, with both literary works under analysis. In Luiz Ruffato's mosaic-novel, we selected, for these essays, fragments of the work that expose problems arising from immigration and family relations; and from Nuno Ramos' tales - or fictional essays - we discuss the use(ful/less) value of art and writing, as well as the human relationship to animal otherness. All the readings undertaken here sought to underline the specificities of the contemporary context without, however, losing sight of the relations established with different historical contexts, aiming to contribute to broadening our understanding of the ways of reading/making Literature today, and how Literature always presents itself as an exciting and renewed way of reading the world.